Measurement and simulation of subsurface tracer migration to tile drains in low permeability, macroporous soil. Issue 6 (7th June 2015) - Bishop, Joshua M.; Callaghan, Michael V.; Cey, Edwin E.; Bentley, Larry R.
Abstract Multiyear monitoring and simulation of a conservative tracer was used in this study to investigate preferential flow and macropore‐matrix interactions in low permeability, macroporous soil. 2, 6‐Difluorobenzoic acid (DFBA) tracer was applied to a 20 × 20 m drip irrigated test plot situated over two tile drains. Tracer movement over the 2009 and 2010 field seasons was monitored using tile drain effluent, suction lysimeters, monitoring wells, and soil cores. Despite similar volumes of water application to the plot in each season, 10 times more water and 14 times more DFBA were captured by the drains in 2010 due to wetter regional hydrologic conditions. The importance of preferential flow along macropores was shown by rapid DFBA breakthrough to the tile (<47 h), and DFBA detections in sand units below the tile drains. Preferential flow resulted in less than 8% of the DFBA mass being captured by the tiles over both years. With much of the DFBA mass (75%) retained in the upper 0.25 m of the soil at the end of 2009, numerical simulations were used to quantify the migration of this in situ tracer during the subsequent 2010 field season. Dual permeability and dual porosity models produced similar matches to measured tile drain flows and concentrations, but solute leaching was captured more effectively by the dual permeability formulation. The simulations highlighted limitations in current descriptions for small‐scale mass transfer between matrix and macropore domains, which do not consider time‐dependent transfer coefficients or nonuniform distributions of solute mass within soil matrix blocks.